Stratification of Al-Maqashid Al-Khamsah (Preserving Religion, Soul, Reason, Heredity and Property) and Its Application in al-Dharuriyah, al-Hajiyah, al-Tahsiniyah, and Mukammilat - Amin, Ibnu; Salma, Salma; Bahar, Muchlis; Lendrawati, Lendrawati (Institut Agama Islam Negeri (IAIN) Curup, 2024)
The stratification of al-maqashid al-khamsah (preserving religion, soul, reason, offspring and property) and its application in al-dharuriyah, al-hajiyah, al-tahsiniyah and al-mukammilat is a study that elaborates the implementation of the objectives of sharia in order to bring benefit and reject the glory of human life. The research method used is library research which is presented in descriptive form from literature that discusses al-maqashid al-khamsah then analyzed. The findings of this study are; The importance of al-maqashid al-khamsah maqashid al-khamsah is the purpose of shari'a to preserve (maintain) the five elements that must exist for the realization of the benefit (al-maslahat) of religion and the world. If this does not exist, it will cause damage (al-mafsadat) and even loss of life and life. There are differences in the opinion of scholars in placing the order of al-maqashid al-khamsah but what is popularly used is the opinion of al-Ghazali, namely hifzh al-din, hifzh al-nafs, hifzh al-'aql, hifzh nasl and hifzh mal. The main objective of sharia is to protect man from harm in five things maqashid al-khamsah safeguarding religion, soul, reason, offspring and property grouped into four strata namely primary needs (al-dharuriyat), secondary (al-hajiyat), complementary (al-tahsiniyat), and perfecter or complement (al-mukammilat)